Hebrews - Beavis, Mary Ann; Kim-Cragg, HyeRan, 1970- (Book collections on Project MUSE., 2015)
Hebrews seems like unpromising material for feminist interpretation, although it is the only New Testament writing for which female authorship has been seriously posited. Mary Ann Beavis and HyeRan Kim-Cragg highlight the similarities between Hebrews and the book of Wisdom/Sophia, which share cosmological, ethical, historical, and sapiential themes, revealing that Hebrews is in fact a submerged tradition of Sophia-Wisdom. They also tackle the sacrificial Christology of Hebrews, concluding that in its ancient context, far from symbolizing suffering and abjection, sacrifice was understood as celebratory and relational. Contributions from Filipina (Maricel and Marilou Ibita), Jewish (Justin Jaron Lewis), historical (Nancy Calvert-Koyzis), and First Nations (Marie Annharte Baker) perspectives bring additional scholarly, cultural, religious, and experiential wisdom to the commentary.